2014
DOI: 10.3390/ijerph110404125
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency Training in Indian Children: A Pilot Investigation of the Penn Resiliency Program

Abstract: This paper examines the effectiveness of the Penn Resiliency Program (PRP) in an urban Indian setting. The PRP is a program to prevent depression in early adolescence and has proved successful in changing children’s attributional style of life events. While the program has been successful in preventing symptoms of depression in Western populations, the current study explored whether this program could be effective with an Indian sample. The aim of the current study was twofold; first, to study the attributiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It was observed as a result of a literature survey that Dray et al (2015) carried out a study on the impacts of general resilience interventions applied at school environment as a result of which it was determined that these intervention programs are effective in reducing the mental health problems of children and adolescents. Similarly, Sankaranarayanan and Cycil (2014) carried out a study examining the impact of resilience program on Indian children as a result of which it was reported that the pessimistic style children used to describe themselves decreased in children who took part in this education while the optimistic style increased. Gillham et al (2006) carried out a study for examining the impact of the resilience program on the depression levels of male adolescents in which it was concluded that the education is not effective in preventing depressive disorder, but that it is effective against multiple disorders in which depression, anxiety and adaptive disorders are observed together.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed as a result of a literature survey that Dray et al (2015) carried out a study on the impacts of general resilience interventions applied at school environment as a result of which it was determined that these intervention programs are effective in reducing the mental health problems of children and adolescents. Similarly, Sankaranarayanan and Cycil (2014) carried out a study examining the impact of resilience program on Indian children as a result of which it was reported that the pessimistic style children used to describe themselves decreased in children who took part in this education while the optimistic style increased. Gillham et al (2006) carried out a study for examining the impact of the resilience program on the depression levels of male adolescents in which it was concluded that the education is not effective in preventing depressive disorder, but that it is effective against multiple disorders in which depression, anxiety and adaptive disorders are observed together.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the reasons for dissatisfaction with life will be collected during the follow-up phases of this longitudinal study. It is important to understand the reasons for dissatisfaction with life at this young age as effective interventions can prevent depression as well as smoking in early adolescence [ 36 , 37 ]. Evidence found that school-based mental health program, especially in the US, has a strong impact on prevention of emotional (the most common is depression) and behavioural problems [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study of the Penn Resiliency Program or PRP in overall society (Challen, Machin, & Gillham, 2014;Cutuli, Gillham, et al, 2013;Gillham et al, 2012;Rebecca K Hodder et al, 2012), which produces the effectiveness and feasibility of school-based resilience interventions through developing mental status and avoidance of emotional or behavioral troubles. Study of the effect of the Penn resilience program conducted in early adolescents in India has found successful in developing children's attribution of life events (Sankaranarayanan & Cycil, 2014). Other resilience program models that investigate and have known effectiveness such as Ready (Burton, Pakenham, & Brown, 2010).…”
Section: Discussionmentioning
confidence: 99%